Preparation method of titanium dioxide with large particle size and high weather resistance

By using single aluminum salt treatment and natural temperature-raising calcining technology in the preparation of titanium dioxide, combined with sand grinding technology, the shortcomings of titanium dioxide in weather resistance and particle size control are solved, and efficient reflection and heat insulation in dark paints are achieved Effectiveness and low-cost production break through the color selection restrictions and expand the application field.

CN119118195APending Publication Date: 2024-12-13SHANDONG DAWN TITANIUM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311804.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing titanium dioxide has shortcomings in weather resistance and particle size control, especially in dark paints, which are difficult to achieve efficient reflection and heat insulation effect, and the preparation process is complex and costly, which limits its application range.

Method used

Using metatitanium acid as the raw material, through single aluminum salt treatment and natural temperature-raising calcining procedures, combined with sand grinding technology, titanium dioxide with large particle size and high weather resistance is prepared to reduce the calcining temperature and improve the uniformity and application performance of the product.

Benefits of technology

It achieves excellent reflective insulation effect in dark paints, improves the overall application performance of titanium dioxide, reduces production energy consumption and costs, extends the service life of the product, and expands its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of titanium dioxide, in particular to a preparation method of titanium dioxide with large particle size and high weather resistance. According to the titanium dioxide, metatitanic acid is used as a raw material, a single aluminum salt treatment mode is adopted, the titanium dioxide with the large particle size can be obtained at the low calcination temperature, and the D50 particle size of the titanium dioxide is 0.9-1.1 [mu] m; in a heat reflection effect test, under the condition of the same color depth, the maximum temperature difference of the titanium dioxide is 5.1 DEG C higher than that of an existing product, in a weather resistance test, under the same test condition, the weather resistance color difference of the titanium dioxide is reduced by half compared with that of the existing product, and the service life of the titanium dioxide is prolonged. The large-particle-size titanium dioxide prepared by the process disclosed by the invention realizes overall breakthrough in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium dioxide, and in particular to a method for preparing titanium dioxide with large particle size and high weather resistance. Background Art

[0002] As a key inorganic chemical raw material, titanium dioxide has a wide range of applications in the fields of inorganic chemical materials, nanotechnology and surface treatment technology, covering multiple industries such as coatings, plastics, rubber, inks, papermaking, textiles and electronics. The main function of titanium dioxide is to provide excellent hiding power, tinting power, weather resistance and light stability, especially weather resistance, which refers to the ability of titanium dioxide to maintain its performance under the influence of environmental factors such as ultraviolet rays, moisture and heat. With the increasing improvement of environmental protection standards, many near-infrared reflective products have emerged on the market. These products have good near-infrared reflective performance, can effectively reflect near-infrared light in sunlight, reduce the internal temperature of objects, and achieve the goals of energy saving and consumption reduction and low-carbon environmental protection. They are suitable for outdoor coatings, surface coatings with special temperature requirements, and military products.

[0003] Patent CN107556801A discloses an iron red near-infrared high-reflective material and a preparation method thereof. The material is based on iron-doped titanium dioxide and is prepared by a sol-gel method to form an innovative material. However, the material is easily affected by external environmental factors and still needs to be improved in terms of weather resistance and durability.

[0004] Patent CN101921517A discloses a dark-colored reflective exterior wall thermal insulation coating and a preparation method thereof. By finely controlling the particle size and particle shape of the pigment filler, the thermal insulation performance of the coating is significantly improved; however, the reflective thermal insulation coating still faces problems such as poor dispersibility and difficulty in particle size control during the preparation process, resulting in insufficient product stability; in addition, the complex preparation process and high cost, as well as the fact that the coating color is mostly limited to white or light colors, limit its application in a wider range of fields.

[0005] In the production of titanium dioxide, its performance can be improved by adding a variety of salts. For example, phosphates can enhance its dispersibility, weather resistance and hydrolysis resistance; potassium salts can change the lattice structure, improve tinting power and hiding power; aluminum salts can improve weather resistance and heat resistance. However, the addition of salts will increase the calcination temperature, affect the lattice structure and grain growth of titanium dioxide, and cause the grains to grow too fast, which in turn leads to a small particle size of titanium dioxide, resulting in a decrease in the performance of titanium dioxide pigments, and even sintering and yellowing and graying of the color. In addition, too high a calcination temperature may affect the integrity of the crystal transformation, reduce its weather resistance, and thus affect the final performance of titanium dioxide. At present, near-infrared reflective products are mostly limited by color, usually light colors, while dark-colored products are difficult to achieve efficient reflective heat insulation effects and cannot meet users' requirements for color; in addition, most existing reflective heat insulation coatings have problems with weather resistance and cannot provide excellent weather resistance. Therefore, developing a titanium dioxide product with large particle size and high weather resistance, while breaking through the color limitations of reflective thermal insulation coatings and achieving excellent reflective thermal insulation effects in dark coatings, has become a technical challenge that needs to be overcome urgently in this field. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a method for preparing titanium dioxide with large particle size, high weather resistance and excellent reflective heat insulation effect in dark coatings. The specific operations are as follows: (1) Raw material selection: using titanic acid as the raw material, the content of iron impurities, phosphate salts, and potassium salts in the raw materials is effectively controlled, and the influence of the raw materials on calcination is reduced, thereby effectively reducing the calcination temperature, reducing the degree of sintering of materials and reducing production energy consumption; (2) Salt treatment method: using a single aluminum salt treatment method, a large-particle titanium dioxide crude product can be obtained at a relatively low temperature during calcination, which reduces production energy consumption and enables the titanium dioxide to have excellent weather resistance, with small color difference under the same conditions, thereby improving its application performance; (3) Sand grinding process :The grinding process of sand mills in series is adopted to make the crude product after calcination fully deagglomerated while ensuring uniform particle size, thereby improving the application performance of the product; (4) Calcination procedure: The calcination procedure with natural heating can effectively control the temperature during the calcination process and avoid sintering of materials caused by excessively high temperatures, thereby obtaining titanium dioxide products with large particle size and high weather resistance; (5) Performance test: Through the weather resistance test experiment, after irradiation in a UV light box for 2 hours, the color difference of each sample before and after aging is measured using a spectrophotometer to evaluate the weather resistance of titanium dioxide; (6) Application test: The prepared titanium dioxide is added as a filler to the reflective heat insulation coating, and its reflective heat insulation effect in the dark coating is tested to evaluate its application performance.

[0007] The specific implementation plan is as follows: A method for preparing large-particle titanium dioxide, comprising the following specific steps: Step 1: Salt Treatment Take the metatitanic acid after the second wash, add desalted water to slurry, control the concentration to 280-320 g / L based on the mass of TiO2 in the metatitanic acid, add Al2(SO4)3 solution, stir for 30-90 min at room temperature, and stir at a rate of 300-400 r / min to obtain slurry; Step 2: Calcination The slurry described in step 1 is filtered, and the obtained filter cake is placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 20-30°C / min. When the temperature reaches above 950°C, the conversion rate is tested every time the temperature rises by 10°C until the conversion rate reaches above 98%, and the calcination is stopped to obtain a crude product; Step 3: Grinding Take the crude product described in step 2, crush it with a universal crusher for 10-20s, then take it out, add desalted water and dispersant to make a slurry, stir it evenly and add it to a sand mill, set the grinding speed to 2000-4000r / min, grind it for 10-20min, then add desalted water, continue grinding for 10-20min, then discharge and take it out to obtain the ground slurry; Step 4: Inorganic treatment Heat the ground slurry in step 3 to 70-90°C, add Na2SiO3 solution at a uniform rate within 1.5-2.5h, stir and mature for 1-1.5h after heating, and the stirring rate is 300-400r / min, then add Al2(SO4)3 solution at a uniform rate within 0.5-1.5h, stir and mature for 1-1.5h after adding, then add NaAlO2 solution at a uniform rate within 0.5-1.5h, stir and mature for 1.5-2.5h after adding, to obtain the coated slurry; Step 5: Wash The coated slurry in step 4 is washed with desalted water and measured with a conductivity meter. The end point of washing is when the conductivity drops below 100uS / cm, and a qualified filter cake is obtained; Step 6: Organic Processing The filter cake that has passed the water washing in step 5 is added with desalted water to be re-slurried, and after being stirred evenly, an organic treatment agent trimethylolpropane (TMP) is added, and the stirring rate is set to 300-350 r / min. After stirring for 30-60 minutes, the mixture is poured into a tray, and placed in an oven. The temperature is adjusted to 110-130° C., and the drying time is 12-24 hours to obtain a dried sample; Step 7: Steam Powder The dried sample in step 6 is first crushed into powder using a universal crusher, and then crushed using a small steam powder mill at a pressure of 0.4-0.6 MPa to obtain large-particle titanium dioxide.

[0008] Furthermore, in step 1, the content of iron impurities in the metatitanic acid after the second washing is below 20 ppm.

[0009] Furthermore, in step 1, the concentration of the Al2(SO4)3 solution is 100-200 g / L, based on the mass of TiO2 in titanic acid as a percentage basis and the mass of Al2(SO4)3, the amount of Al2(SO4)3 added in the solution is controlled to be 0.2%-0.6% of TiO2.

[0010] Furthermore, in the test conversion rate in step 2, since calcination converts amorphous titanium dioxide into a rutile structure, the conversion rate can be obtained by testing the content of the rutile structure. The content of the rutile structure, i.e., the conversion rate, can be confirmed by conventional detection means, such as XRD, Raman spectroscopy, infrared spectroscopy, TEM, SEM, and thermogravimetric analysis.

[0011] Furthermore, in step 3, the ratio of the crude product to desalted water is 800-1200 mL of desalted water for every 500 g of the crude product; the dispersant is an aqueous solution of either Na2SiO3 or sodium hexametaphosphate, and based on the mass of the crude product as a percentage, the amount of Na2SiO3 added is controlled to be 0.15-0.5% of the crude TiO2 product in terms of the mass of Na2SiO3; based on the mass of the crude product as a percentage, the amount of sodium hexametaphosphate added is controlled to be 0.15-0.5% of the crude TiO2 product in terms of the mass of sodium hexametaphosphate.

[0012] Further, 2-10 mL of the ground slurry described in step 3 is taken, 100-500 mL of ultrapure water is added, and 5-25 mL of sodium hexametaphosphate with a mass fraction of 1-5% is added as a dispersant, and a particle size test is performed to obtain a crude product with a D50 particle size of 0.9-1.1 μm.

[0013] Further, in step 4, the concentration of the Na2SiO3 solution is 100-200 g / L, and based on the mass of the crude product in step 2 as a percentage basis, the amount of Na2SiO3 added to the crude product is controlled to be 1.8-2.2% by mass of Na2SiO3; the concentration of the Al2(SO4)3 solution is 100-200 g / L, and based on the mass of the crude product in step 2 as a percentage basis, the amount of Al2(SO4)3 added to the crude product is controlled to be 1.3-1.7% by mass of Al2(SO4)3; the concentration of the NaAlO2 solution is 100-200 g / L, and based on the mass of the crude product in step 2 as a percentage basis, the amount of NaAlO2 added to the crude product is controlled to be 1.4-1.8%.

[0014] Furthermore, in step 6, during the re-slurrying, 800-1000 mL of water is added to every 500 g of the qualified filter cake after washing, and the amount of TMP added is 0.1-0.5% of the crude product in terms of the mass of TMP, based on the mass of the crude product in step 2.

[0015] Further, in step 7, the D50 particle size of the large-particle titanium dioxide is expressed as 0.9-1.1 μm.

[0016] Furthermore, the performance test of the aforementioned large-particle titanium dioxide is carried out, and the specific steps are as follows: (1) Sample preparation: Take 12-20g of polyester resin, 2-8g of black paint, and 6-60g of the large-particle titanium dioxide according to claim 1, and grind and disperse them in a dual-center mixing and dispersing machine for 5-40min at a grinding speed of 1000-4000r / min to obtain a sample to be tested, wherein the black paint is prepared by mixing the red paint and the green paint of the polyester paint in a mass ratio of 1:1; (2) Plate preparation: The sample to be tested is coated on a test-grade tinplate plate using a 150-500 μm wet film preparation device, with a film thickness of 50-500 μm, and then placed in an oven for drying at 90-200° C. to obtain a sample plate to be tested; (3) Cooling effect test: Calibration: Place two calibration plates coated with black enamel in front of two infrared lamps with a wavelength of 850-1500nm and an intensity of 200-1000mW / sr. Adjust the distance between the standard plate and the lamp so that the temperature difference between the test areas on the back of the two standard plates is ≤0.5℃. Record the initial temperature. Test: Remove the standard plate on the right side and install the sample plate to be tested. Test the temperature of the test area on the back of the two samples at 5 minutes, 10 minutes and 15 minutes respectively, and calculate the temperature difference between the test plates of different samples and the standard plate; (4) Weathering test: Place the sample to be tested in a UV light box for 2-10 hours, and use a spectrophotometer to measure the color difference of each sample before and after aging.

[0017] The beneficial effects of the present invention are as follows: 1. The present invention uses a single aluminum salt to treat the metatitanic acid raw material through innovative salt treatment technology, successfully reducing the calcination temperature. Compared with the traditional salt treatment method, the present invention can prepare large-particle titanium dioxide at a lower temperature. This improvement not only reduces the energy consumption in the production process, but also gives the titanium dioxide excellent weather resistance, and unexpectedly makes the titanium dioxide show excellent performance in dark coatings, with good reflective heat insulation effect and small color difference, breaking the limitation of reflective heat insulation coatings in color selection and realizing its efficient application in dark coatings; these characteristics not only improve the overall application performance of titanium dioxide, but also expand its application field; 2. The present invention provides a method for preparing titanium dioxide with large particle size and high weather resistance, which effectively solves the problem in the prior art that titanium dioxide has small particle size and needs further processing. The method of the present invention can directly prepare titanium dioxide with large particle size, which can meet the requirements of certain special applications without further processing, such as application in reflective heat insulation coatings; 3. The preparation method of the present invention does not require a large amount of energy and chemical reagents, has low cost, and has less environmental pollution. Compared with the existing sulfuric acid method, chlorination method and reduction method, it has obvious environmental and economic advantages; 4. The titanium dioxide of the present invention can ensure the long-term stability of the film performance due to its high weather resistance, and effectively prevent the occurrence of problems such as hue change and powdering. Compared with the existing titanium dioxide on the market, the product of the present invention has a longer service life and higher performance stability. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be described in detail below in conjunction with specific embodiments of the present invention. The described embodiments are only a part of the present invention, and the present invention is not limited to the embodiments described below.

[0019] Example 1 (The difference between Examples 1-3 is only the difference in the amount of Al2(SO4)3 solution added in step 1. Three substances are added in step 1 of Comparative Example 1, and two substances are added in step 1 of Comparative Example 2. The difference is highlighted in bold) The large-particle titanium dioxide sample 1 is prepared by: Step 1: Salt Treatment Take 2000g of the metatitanic acid after the second wash, add 500mL of desalted water for slurrying, and control the concentration at 310g / L based on the mass of TiO2 in the metatitanic acid. Take 2000mL of the slurry after slurrying, add 15.5mL of 100g / L Al2(SO4)3 solution, stir and disperse for 60min at a stirring rate of 350r / min to obtain slurry 1; Step 2: Calcination The slurry described in step 1 was filtered, and the obtained filter cake was placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 24°C / min. When the temperature reached above 950°C, 5 g of the calcined product was taken at intervals of 10°C to test the conversion rate until the conversion rate reached 98%, and the calcination was stopped to obtain a crude product 1; Step 3: Grinding Take 500g of the crude product 1 in step 2, crush it with a universal grinder for 10s, then take it out, add 1000mL of desalted water and 15mL of 100g / L Na2SiO3 solution to make a slurry, stir evenly and add it to a sand mill, set the grinding speed to 2000r / min, grind for 15min, then add 200mL of desalted water, continue grinding for 15min, then discharge and take out the ground slurry 1; Take 2 mL of the ground slurry 1, add 100 mL of ultrapure water, add 5 mL of 1% sodium hexametaphosphate as a dispersant, perform a particle size test, and record the D50 particle size of the crude product 1; Step 4: Inorganic treatment Heat the slurry 1 after grinding in step 3 to 80°C, add 100 mL of 100 g / L Na2SiO3 solution at a uniform speed within 2 hours, stir and mature for 1 hour after the addition is completed, then add 75 mL of 100 g / L Al2(SO4)3 solution at a uniform speed within 1 hour, stir and mature for 1 hour after the addition is completed, then add 80 mL of 100 g / L NaAlO2 solution at a uniform speed within 1 hour, stir and mature for 2 hours after the addition is completed, to obtain the coated slurry 1, the stirring rate is 350 r / min; Step 5: Wash The coated slurry 1 in step 4 is washed with desalted water and measured with a conductivity meter. When the conductivity drops to 80uS / cm, the washing is terminated to obtain a qualified filter cake 1; Step 6: Organic Processing Take 500g of the filter cake 1 after washing in step 5, add 800mL of desalted water, stir evenly, add 1.5g of TMP, set the stirring rate to 300r / min, stir for 30min, pour into a tray, put into an oven, adjust the temperature to 120°C, and dry for 12h to obtain the dried sample 1; Step 7: Steam Powder The sample 1 dried in step 6 is first crushed into powder using a universal crusher, and then crushed using a small steam powder mill under a pressure of 0.4 MPa to obtain a crushed sample, which is recorded as sample 1; Take 0.5 g of the sample 1, add 100 mL of ultrapure water and 5 mL of 1% sodium hexametaphosphate as a dispersant, and perform a particle size test, mainly recording the D50 particle size of the sample 1.

[0020] Example 2 Large particle size titanium dioxide sample 2, the preparation method comprises: Step 1: Salt Treatment Take 2000g of the metatitanic acid after the second wash, add 500mL of desalted water for slurrying, and control the concentration at 310g / L based on the mass of TiO2 in the metatitanic acid. Take 2000mL of the slurry after slurrying, add 21.7mL of 100g / L Al2(SO4)3 solution, stir and disperse for 60min at a stirring rate of 350r / min to obtain slurry 2; Step 2: Calcination The slurry described in step 1 was filtered, and the obtained filter cake was placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 24°C / min. When the temperature reached above 950°C, 5 g of the calcined product was taken at intervals of 10°C to test the conversion rate until the conversion rate reached 98%, and the calcination was stopped to obtain a crude product 2; Step 3: Grinding Take 500g of the crude product 2 in step 2, crush it with a universal grinder for 10s, then take it out, add 1000mL of desalted water and 15mL of 100g / L Na2SiO3 solution to make a slurry, stir evenly and add it to a sand mill, set the grinding speed to 2000r / min, grind for 15min, then add 200mL of desalted water, continue grinding for 15min, then discharge and take out the ground slurry 2; Take 2 mL of the ground slurry 2, add 100 mL of ultrapure water, add 5 mL of 1% sodium hexametaphosphate as a dispersant, perform a particle size test, and record the D50 particle size of the crude product 2; Step 4: Inorganic treatment Heat the slurry 2 after grinding in step 3 to 80°C, add 100 mL of 100 g / L Na2SiO3 solution at a uniform speed within 2 hours, stir and mature for 1 hour after the addition is completed, then add 75 mL of 100 g / L Al2(SO4)3 solution at a uniform speed within 1 hour, stir and mature for 1 hour after the addition is completed, then add 80 mL of 100 g / L NaAlO2 solution at a uniform speed within 1 hour, stir and mature for 2 hours after the addition is completed, to obtain the coated slurry 2, the stirring rate is 350 r / min; Step 5: Wash The coated slurry 2 in step 4 is washed with desalted water and measured with a conductivity meter. When the conductivity drops to 80uS / cm, the washing is terminated to obtain a qualified filter cake 2; Step 6: Organic Processing Take 500g of the filter cake 2 after washing in step 5, add 800mL of desalted water, stir evenly, add 1.5g of TMP, set the stirring rate to 300r / min, stir for 30min, pour into a tray, put into an oven, adjust the temperature to 120°C, and dry for 12h to obtain the dried sample 2; Step 7: Steam Powder The sample 2 dried in step 6 is first crushed into powder using a universal crusher, and then crushed using a small steam powder mill under a pressure of 0.4 MPa to obtain a crushed sample, which is recorded as sample 2; Take 0.5 g of the sample 2, add 100 mL of ultrapure water and 5 mL of 1% sodium hexametaphosphate as a dispersant, and perform a particle size test, mainly recording the D50 particle size of the sample 2.

[0021] Example 3 Large particle size titanium dioxide sample 3, the preparation method comprises: Step 1: Salt Treatment Take 2000g of the metatitanic acid after the second wash, add 500mL of desalted water for slurrying, and control the concentration at 310g / L based on the mass of TiO2 in the metatitanic acid. Take 2000mL of the slurry, add 27.9mL of 100g / L Al2(SO4)3 solution, stir and disperse for 60min at a stirring rate of 350r / min to obtain slurry 3; Step 2: Calcination The slurry described in step 1 was filtered, and the obtained filter cake was placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 24°C / min. When the temperature reached above 950°C, 5 g of the calcined product was taken at intervals of 10°C to test the conversion rate until the conversion rate reached 98%, and the calcination was stopped to obtain a crude product 3; Step 3: Grinding Take 500g of the crude product 3 in step 2, crush it with a universal grinder for 10s, then take it out, add 1000mL of desalted water and 15mL of 100g / L Na2SiO3 solution to make a slurry, stir evenly and add it to a sand mill, set the grinding speed to 2000r / min, grind for 15min, then add 200mL of desalted water, continue grinding for 15min, then discharge and take out the ground slurry 3; Take 2 mL of the ground slurry 3, add 100 mL of ultrapure water, add 5 mL of 1% sodium hexametaphosphate as a dispersant, perform a particle size test, and record the D50 particle size of the crude product 3; Step 4: Inorganic treatment Heat the slurry 3 after grinding in step 3 to 80°C, add 100 mL of 100 g / L Na2SiO3 solution at a uniform speed within 2 hours, stir and mature for 1 hour after the addition is completed, then add 75 mL of 100 g / L Al2(SO4)3 solution at a uniform speed within 1 hour, stir and mature for 1 hour after the addition is completed, then add 80 mL of 100 g / L NaAlO2 solution at a uniform speed within 1 hour, stir and mature for 2 hours after the addition is completed, to obtain the coated slurry 3, the stirring rate is 350 r / min; Step 5: Wash The coated slurry 3 in step 4 is washed with desalted water and measured with a conductivity meter. When the conductivity drops to 80uS / cm, the washing is terminated to obtain a qualified filter cake 3; Step 6: Organic Processing Take 500g of the filter cake 3 after washing in step 5, add 800mL of desalted water, stir evenly, add 1.5g of TMP, set the stirring rate to 300r / min, stir for 30min, pour into a tray, put into an oven, adjust the temperature to 120°C, and dry for 12h to obtain the dried sample 3; Step 7: Steam Powder The sample 3 dried in step 6 is first crushed into powder using a universal crusher, and then crushed using a small steam powder mill under a pressure of 0.4 MPa to obtain a crushed sample, which is recorded as sample 3; Take 0.5 g of the sample 3, add 100 mL of ultrapure water and 5 mL of 1% sodium hexametaphosphate as a dispersant, and perform a particle size test, mainly recording the D50 particle size of the sample 3.

[0022] Comparative Example 1 Titanium dioxide sample 4, the preparation method comprises: Step 1: Salt Treatment Take 2000g of the metatitanic acid after the second wash, add 500mL of desalted water for slurrying, and control the concentration at 310g / L based on the mass of TiO2 in the metatitanic acid. Take 2000mL of the slurry after slurrying, add 8.06mL of 100g / L phosphoric acid solution, stir and disperse for 60min, add 12.4mL of 300g / L KOH solution, stir and disperse for 60min; add 21.7mL of 100g / L Al2(SO4)3 solution, stir and disperse for 60min, and the stirring rate is 350r / min to obtain slurry 4; Step 2: Calcination The slurry described in step 1 was filtered, and the obtained filter cake was placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 24°C / min. When the temperature reached above 950°C, 5 g of the calcined product was taken at intervals of 10°C, ground into fine powder with a mortar, pressed into tablets, and subjected to XRD testing. The conversion rate was read on a computer supporting the instrument until the conversion rate reached 98%, and the calcination was stopped to obtain a crude product 4; Step 3: Grinding Take 500g of the crude product 4 in step 2, crush it with a universal grinder for 10s, then take it out, add 1000mL of desalted water and 15mL of 100g / L Na2SiO3 solution to make a slurry, stir evenly and add it to a sand mill, set the grinding speed to 2000r / min, grind for 15min, then add 200mL of desalted water, continue grinding for 15min, then discharge and take out the ground slurry 4; Take 2 mL of the ground slurry 4, add 100 mL of ultrapure water, add 5 mL of 1% sodium hexametaphosphate as a dispersant, perform a particle size test, and record the D50 particle size of the crude product 4; Step 4: Inorganic treatment Heat the slurry 4 after grinding in step 3 to 80°C, add 100 mL of 100 g / L Na2SiO3 solution at a uniform speed within 2 hours, stir and mature for 1 hour after the addition is completed, then add 75 mL of 100 g / L Al2(SO4)3 solution at a uniform speed within 1 hour, stir and mature for 1 hour after the addition is completed, then add 80 mL of 100 g / L NaAlO2 solution at a uniform speed within 1 hour, stir and mature for 2 hours after the addition is completed, to obtain the coated slurry 4, the stirring rate is 350 r / min; Step 5: Wash The coated slurry in step 4 is washed with desalted water and measured with a conductivity meter. When the conductivity drops to 80uS / cm, the washing is terminated to obtain a qualified filter cake 4; Step 6: Organic Processing Take 500g of the filter cake that has passed the water washing in step 5, add 800mL of desalted water, re-slurry, stir evenly, add 1.5g of TMP, set the stirring rate to 300r / min, stir for 30min, pour into a tray, put into an oven, adjust the temperature to 120°C, and dry for 12h to obtain the dried sample 4; Step 7: Steam Powder The sample 4 dried in step 6 is first crushed into powder using a universal crusher, and then crushed using a small steam powder mill under a pressure of 0.4 MPa to obtain a crushed sample, which is recorded as sample 4; Take 0.5 g of the sample 4, add 100 mL of ultrapure water and 5 mL of 1% sodium hexametaphosphate as a dispersant, and perform a particle size test, mainly recording the D50 particle size of the sample 4.

[0023] Comparative Example 2 Titanium dioxide sample 5, the preparation method comprises: Step 1: Salt Treatment Take 2000g of the metatitanic acid after the second wash, add 500mL of desalted water for slurrying, and control the concentration at 310g / L based on the mass of TiO2 in the metatitanic acid. Take 2000mL of the slurry after slurrying, add 12.4mL of 300g / L KOH solution, stir and disperse for 60min, add 21.7mL of 100g / L Al2(SO4)3 solution, stir and disperse for 60min, and the stirring rate is 350r / min to obtain slurry 5; Step 2: Calcination The slurry described in step 1 was filtered, and the obtained filter cake was placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 24°C / min. When the temperature reached above 950°C, 5 g of the calcined product was taken at intervals of 10°C, ground into fine powder with a mortar, pressed into tablets, and subjected to XRD testing. The conversion rate was read on a computer supporting the instrument until the conversion rate reached 98%, and the calcination was stopped to obtain a crude product 5; Step 3: Grinding Take 500g of the crude product 5 in step 2, crush it with a universal grinder for 10s, then take it out, add 1000mL of desalted water and 15mL of 100g / L Na2SiO3 solution to make a slurry, stir evenly and add it to a sand mill, set the grinding speed to 2000r / min, grind for 15min, then add 200mL of desalted water, continue grinding for 15min, then discharge and take out the ground slurry 5; Take 2 mL of the ground slurry 5, add 100 mL of ultrapure water, add 5 mL of 1% sodium hexametaphosphate as a dispersant, perform a particle size test, and record the D50 particle size of the crude product 5; Step 4: Inorganic treatment Heat the slurry after grinding in step 3 to 80°C, add 100 mL of 100 g / L Na2SiO3 solution at a uniform speed within 2 hours, stir and mature for 1 hour after the addition is completed, then add 75 mL of 100 g / L Al2(SO4)3 solution at a uniform speed within 1 hour, stir and mature for 1 hour after the addition is completed, then add 80 mL of 100 g / L NaAlO2 solution at a uniform speed within 1 hour, stir and mature for 2 hours after the addition is completed, to obtain the coated slurry 5; Step 5: Wash The coated slurry 5 in step 4 is washed with desalted water and measured with a conductivity meter. When the conductivity drops to 80uS / cm, the washing is terminated to obtain a qualified filter cake 5; Step 6: Organic Processing Take 500g of the filter cake 5 after washing in step 5, add 800mL of desalted water, stir evenly, add 1.5g of TMP, set the stirring rate to 300r / min, stir for 30min, pour into a tray, put into an oven, adjust the temperature to 120°C, and dry for 12h to obtain the dried sample 5; Step 7: Steam Powder The sample 5 dried in step 6 is first crushed into powder using a universal crusher, and then crushed using a small steam powder mill under a pressure of 0.4 MPa to obtain a crushed sample, which is recorded as sample 5; Take 0.5 g of the sample 5, add 100 mL of ultrapure water and 5 mL of 1% sodium hexametaphosphate as a dispersant, and perform a particle size test, mainly recording the D50 particle size of the sample 5.

[0024]

[0025] Cooling effect test (1) Sample preparation: Take 12g of polyester resin, 2g of black paint, and 6g of the aforementioned titanium dioxide samples 1-5, grind and disperse them in a dual-center mixing and dispersing machine for 5 minutes at a grinding speed of 2000r / min to obtain samples 1-5 to be tested. The black paint is prepared by mixing the red paint and the green paint of the polyester paint in a mass ratio of 1:1; (2) Plate preparation: The samples 1-5 to be tested are coated on a test-grade tinplate plate using a 150 μm wet film preparation device, with a film thickness of 150 μm, and then placed in an oven for drying at 90° C. to obtain the test samples 1-5; (3) Cooling effect test: Calibration: Place two calibration plates coated with black magnetic paint in front of two infrared lamps with a wavelength of 850nm and an intensity of 200mW / sr. Adjust the distance between the standard plate and the lamp so that the temperature difference between the test areas on the back of the two standard plates is ≤0.5℃. Record the initial temperature. Test: remove the standard plate on the right side, and install the test sample 1 in turn, test the temperature of the test area on the back of the left and right samples at 5min, 10min, and 15min respectively, and calculate the temperature difference between the test sample 1 and the standard plate; Repeat this operation until all the test samples 1-5 are tested.

[0026] Weathering test experiment Place the test samples 1-5 in a UV light box for 2 hours, and use a spectrophotometer to measure the color difference of each sample before and after aging.

[0027] Table 3. Cooling effect and weather resistance test results

[0028] It is common knowledge in the prior art that the darker the color, the worse the heat reflection efficiency of titanium dioxide. However, the present application optimizes the preparation method of titanium dioxide and achieves that under the same color depth (red paint and green paint are prepared in a mass ratio of 1:1), the maximum temperature difference in Example 2 is 36.1°C, and the temperature difference in Comparative Example 1 is only 31°C. The heat reflection effect of Example 2 is 5.1°C higher than that of Comparative Example 1, indicating that the titanium dioxide product of the present invention is significantly superior to similar products in the prior art in terms of heat reflection effect. It can be used in the fields of outdoor coatings to effectively reduce indoor temperature and achieve energy saving and consumption reduction. The weathering color difference of Example 2 is 2.8, and the weathering color difference of Comparative Example 1 is 5.5. The weathering color difference of the titanium dioxide product of the present invention is reduced by nearly half compared with that of ordinary samples, and the weathering performance is significantly improved, which effectively prevents yellowing of the coating. Therefore, the large-particle titanium dioxide of the present invention has achieved an overall breakthrough in performance.

[0029] The above-mentioned embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solution of the present invention in detail, but it cannot be understood as limiting the scope of the invention patent protection. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing large-particle titanium dioxide, It is characterized in that The specific steps are: Step 1: Salt Treatment Take titanic acid, add desalted water to make pulp, and use the TiO 2 Mass meter, control the concentration at 280-320g / L, add Al 2 (SO 4 ) 3 The solution was stirred at room temperature for 30-90 min at a stirring rate of 300-400 r / min to obtain a slurry; Step 2: Calcination The slurry described in step 1 is filtered, and the obtained filter cake is placed in a muffle furnace and calcined according to a natural heating program at a heating rate of 20-30°C / min. When the temperature reaches above 950°C, the conversion rate is tested every time the temperature rises by 10°C until the conversion rate reaches above 98%, and the calcination is stopped to obtain a crude product; Step 3: Grinding Take the crude product described in step 2, crush it with a universal crusher for 10-20s, then take it out, add desalted water and dispersant to make a slurry, stir it evenly and add it to a sand mill, set the grinding speed to 2000-4000r / min, grind it for 10-20min, then add desalted water, continue grinding for 10-20min, then discharge and take it out to obtain the ground slurry; Step 4: Inorganic treatment The ground slurry described in step 3 was heated to 70-90°C and Na 2 SiO 3 Solution, Al 2 (SO 4 ) 3 Solution, NaAlO 2 The solution is heated and matured to obtain a coated slurry; Step 5: Wash The coated slurry in step 4 is washed with desalted water and measured with a conductivity meter. The end point of the washing is when the conductivity drops below 100uS / cm, and a qualified filter cake is obtained; Step 6: Organic Processing The filter cake after washing in step 5 is added with desalted water for re-slurrying, and after stirring evenly, trimethylolpropane, an organic treatment agent, is added, and the stirring rate is set to 300-350 r / min. After stirring for 30-60 min, the mixture is poured into a tray, and placed in an oven. The temperature is adjusted to 110-130° C., and the drying time is 12-24 h to obtain a dried sample; Step 7: Steam Powder The dried sample in step 6 is crushed to obtain large-particle titanium dioxide.

2. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 1, the content of iron impurities in the metatitanic acid is below 20 ppm.

3. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 1, the Al 2 (SO 4 ) 3 The solution concentration is 100-200g / L, based on TiO 2 The percentage is based on mass, with Al 2 (SO 4 ) 3 Mass meter, Al 2 (SO 4 ) 3 The solution is controlled in Al 2 (SO 4 ) 3 The amount of TiO added 2 0.2-0.6%.

4. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 3, the ratio of the crude product to desalted water is 800-1200 mL of desalted water per 500 g of crude product; the dispersant is Na 2 SiO 3 Or sodium hexametaphosphate, any one of the aqueous solutions, based on the crude mass as the percentage basis, Na 2 SiO 3 Mass meter, dispersant controlled at Na 2 SiO 3 The amount of TiO added is 2 0.15-0.5% of the crude product; based on the crude product mass as the percentage basis, the dispersant is controlled at an amount of sodium hexametaphosphate added of TiO 2 0.15-0.5% of crude product.

5. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that The slurry after grinding described in step 3 was taken for particle size test, and the D50 particle size of the crude product was 0.9-1.1 μm.

6. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 4, the ground slurry is heated to 70-90°C and Na is added at a constant rate over 1.5-2.5 hours. 2 SiO 3 After heating, stir and ripen the solution for 1-1.5h at a stirring rate of 300-400r / min, then add Al at a uniform rate within 0.5-1.5h. 2 (SO 4 ) 3 After adding the solution, stir and mature for 1-1.5h, then add NaAlO at a uniform rate within 0.5-1.5h. 2 After adding the solution, stir and mature for 1.5-2.5 hours to obtain the coated slurry.

7. The method for preparing large-particle titanium dioxide according to any one of claims 1 or 6, It is characterized in that In step 4, the Na 2 SiO 3 The concentration of the solution is 100-200 g / L, based on the mass of the crude product as the percentage, and the Na 2 SiO 3 Mass meter, Na 2 SiO 3 The solution is controlled at Na 2 SiO 3 The amount of Al added is 1.8-2.2% of the crude product; 2 (SO 4 ) 3 The concentration of the solution is 100-200 g / L, based on the mass of the crude product as the percentage basis, and Al 2 (SO 4 ) 3 Mass meter, Al 2 (SO 4 ) 3 The solution is controlled in Al 2 (SO 4 ) 3 The addition amount is 1.3-1.7% of the crude product; the NaAlO 2 The concentration of the solution is 100-200 g / L, based on the mass of the crude product, and the NaAlO 2 Mass meter, NaAlO 2 The solution is controlled in NaAlO 2 The amount added is 1.4-1.8% of the crude product.

8. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 6, during the re-slurrying, 800-1000 mL of water is added to every 500 g of the qualified filter cake after washing, and the amount of TMP added is 0.1-0.5% of the crude product in terms of the mass of TMP, based on the mass of the crude product.

9. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 7, the pulverization is performed by pulverizing the dried sample at a pressure of 0.4-0.6 MPa using a small steam pulverizer.

10. The method for preparing large-particle titanium dioxide according to claim 1, It is characterized in that In step 7, the D50 particle size of the large-particle titanium dioxide is 0.9-1.1 μm.